Curious Cases of Copyrightability Before the Copyright Office - Smith, Regan A. (The Columbia Journal of Law & the Arts, 2020)
Administering the national registration program is a core function of the Copyright Office. In most cases, determining copyrightability of a claim submitted for registration is simple, and the Office does not need to correspond over or otherwise belabor the mine run of applications to determine whether a work possesses the creative spark necessary to register a copyright interest. As the Supreme Court has noted, “the requisite level of creativity is extremely low,” and “[t]he vast majority of works make the grade quite easily.” Sometimes, however, applied-for works invoke modes of authorship that test that standard, and the Copyright Office must resolve these claims. Applicants may contest refusals to register claims, culminating in the ability to lodge a final administrative appeal to the Copyright Office Review Board. As a member of that Board for the past four years, I’ve seen the Office apply established principles of copyrightability to a variety of dynamic claims.